Эволюция высшей нервной деятельности: (очерки) / Л. Г. Воронин - Воронин Леонид Григорьевич (Наука, 1977)
Экземпляры: КХ (20140624) / Инвентарный номер: 655836 / Цена: 0.71 / Сис.шифр: 612.8 / Авт.знак: В 75 / ГРНТИ: 76 / ББК: 5